Reliability of digitized cheiloscopy, dactyloscopy and combination approach for gender identification - A comparative study - Ajay Pal Singh Kataria; Aravinda Konidena; Gagan Puri; Deepa Jatti Patil; Rajesh Gupta (Wolters Kluwer Medknow Publications, 2020)
Background and Aims: The oral cavity allows for a numerous prospects for personal identification of subjects. Dental profiling, palatoscopy, cheiloscopy had enabled in nailing the suspects in addition to traditional methods like anthropometry, finger prints, blood groups, DNA analysis. The aim of this study is to assess the reliability of digitized lip prints, finger prints and combination approach in gender determination in Panchkula population. Method: A total of 500 healthy subjects, (250 females and 250 males) aged 20 to 30 years of both genders were recruited and evaluated. Lip prints were obtained by painting lip stick and using cellotape to take the impression, while finger prints were obtained by fingerprint rolling technique. Scanned images of the obtained lip and finger prints were analyzed according to Suzuki K and Tsuchihashi Y and classification by Cummins and Midlo, respectively, using applications of 'Adobe Photoshop 7' software. Results: Finger print analysis correctly classified gender in 52.6%, but was not statistically significant (Canonical correlation = 0.117, P = 0.230) Lip print analysis correctly identified gender in 64.8% and was statistically significant (Canonical correlation = 0.350,P < 0.001). When a combination approach was used, the gender was correctly identified in 65.8% and was statistically significant (Canonical correlation = 0.369,P < 0.001). Conclusion: Although not a 100% accurate method, the combination method was found to be more accurate and thus can be used as a supplementary tool in sex determination.